EXPERIMENTAL STUDIES OF VIBRATIONS OF STRUCTURES OF THE TYPE "TRANSPORT-LAUNCH CONTAINER - ROCKET" DURING TRANSPORTATION - KOVTUN, ANATOLY; TABUNENKO, VOLODYMYR; GUNBIN, KOSTYANTYN; SALNYK, OLEG (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The development of a modern domestic mobile missile complex for operational and tactical purposes is one of the most important tasks facing military scientists. The operation of the components of a mobile launcher with a missile under the action of external loads is a complex process that is difficult to describe in all its variety of features. Therefore, when starting to design complex structures, it is important to determine which factors are significant for them, and which can be neglected without losing their performance. The main design case for ground operation of mobile missile complex units is the case of transportation rocket in a transport-launch container with an attached head part. In modern designs of mobile launchers, the rocket, during the production process, is placed in a transport-launch container (TLC), with which its further operation is associated. Such placement of the rocket forms a mechanical system "Transport and Launch Container - Rocket" (TPK - R), the connection between which is created by the friction force between their surfaces, which form a nonlinear non-destructive connection that allows the components of the mechanical system to move relative to each other, while changing the dynamic properties of the entire structure. However, when designing mechanical systems "Transport and launch container - Rocket" during transportation, a calculation scheme of connecting the rocket to the TPK with hinged supports is often used, which does not take into account the real conditions of their interaction with each other. The aim of the work was to experimentally determine the spectrum of natural frequencies of oscillations of structures of the TPK-R type, the components of which are interconnected by the force of dry friction. Based on the set goal, an experimental setup was created to study the dynamic characteristics of structures of the TPK-R type. Results the conducted experimental studies allow us to draw the following conclusions: - with the increase in the friction force in the supports, the resonant frequency of the rocket model increases. The first resonant frequency of the rocket model with friction supports is 1.4 times higher than the first resonant frequency of the rocket model on hinged supports; - TPK-R type structures must be considered as structures with significantly nonlinear dissipative forces. Analysis of the obtained regression equations allowed us to draw the following conclusions: - the value of the resonant frequency of the rocket model is most significantly influenced by the friction force in the third support; - the magnitude of the resonant amplitude of oscillations is most significantly influenced by the friction force in the second and third supports; with its increase, the magnitude of the system response decreases; - in addition, along with linear effects, the interaction of three factors has a significant impact on the magnitude of the initial response, and this interaction has the opposite effect on the initial response; - the location of the first support has the greatest influence on the magnitude of the resonant frequency of oscillations of the cantilever part of the rocket model; - the location of the first and third supports has the greatest influence on the magnitude of the resonant amplitude of oscillations of the cantilever part of the rocket model. Thus, to increase the frequency and decrease the amplitude of the resonant oscillations of the rocket model, it is necessary to increase the friction force in the supports. The practical value of the results obtained lies in taking into account the real connections between the rocket and the transport and launch container, which ensures increased safety of the rockets during transportation.